The Interplay of Food Insecurity, Resilience, Stress Mindset, and Mental Distress: Insights From a Cross‐Sectional Study - Lina Begdache; Amera Al‐Amery; Katerina K. Nagorny; Ushima Chowdhury; Lexis R. Rosenberg; Zeynep Ertem (Health Science Reports)
ABSTRACT Background and Aims In the United States, food insecurity (FI) is a serious health issue potentially affecting brain function. While neuroimaging suggests that diet quality influences brain functions, gaps remain regarding its impact on resilience, stress mindset, and mental distress, particularly across age and gender. This cross‐sectional study investigated these relationships using data from 1099 participants, of whom 26.19% were females and 70.39% were males, with the majority (70%) being under 30 years. Methods A multi‐scale questionnaire assessing FI, resilience, stress mindset, and mental distress was distributed via social media. ANOVA and Ordinary Least Squares (OLS) regression were used to analyze the data in Python. Results FI was linked to reduced resilience and increased mental distress (p < 0.05), but did not produce an effect on stress mindset. Age, gender, education, and physical activity influenced neurobehaviors (p < 0.01), with physical activity showing the greatest improvement in resilience. Women exhibited stronger correlations between FI and neurobehaviors than men. Conclusion Encouraging physical activity and targeted mental health interventions can enhance resilience and reduce distress, particularly in women. Community‐based programs addressing gender and age disparities may be key to improving mental well‐being.